The Optimal Reverberation for Masjids: A Subjective Assessment for Worshippers’ Demands - Elkhateeb, Ahmed; Eldakdoky, Soha (International Journal of Architectural Engineering Technology, 2022)
This study investigates the optimal reverberation time in masjids (mosques) from worshippers’ viewpoint for the two modes of performance: recitation and sermon/speech. It also examines the effect of both age and gender on worshippers’ preferences. To this end, specially convolved five audio clips (five acoustic setups) for each mode were created and uploaded to Google Drive. More than 300, Arabic-speaking participants, males, and females of different ages, listened to these clips. The participants judged the quality (Q, or appropriateness) of these audio clips for listening either to the recitation (QR) or speech (QS) on a unipolar discrete five-grade scale via a questionnaire that was created on Google Forms. Results indicated that both QR and QS are functions of gender and age. Overall, younger worshippers preferred higher reverberation and vice versa, while gender significantly affected the perception of the desirable reverberation for both recitation and speech. Females tended to the shorter reverberant environment (1.38 s for recitation mode, 0.75 s for speech mode, in the mid-frequency range) than males who preferred longer reverberation for recitation in particular (1.77 s).